Cancer risk in MLH1, MSH2 and MSH6 mutation carriers; different risk profiles may influence clinical management - Ramsoekh, Dewkoemar (BioMed Central, 2009)
BACKGROUND: Lynch syndrome (LS) is associated with a high risk for colorectal cancer (CRC) and extracolonic malignancies, such as endometrial carcinoma (EC). The risk is dependent of the affected mismatch repair gene. The aim of the present study was to calculate the cumulative risk of LS related cancers in proven MLH1, MSH2 and MSH6 mutation carriers. METHODS: The studypopulation consisted out of 67 proven LS families. Clinical information including mutation status and tumour diagnosis was collected. Cumulative risks were calculated and compared using Kaplan Meier survival analysis. RESULTS: MSH6 mutation carriers, both males and females had the lowest risk for developing CRC at age 70 years, 54% and 30% respectively and the age of onset was delayed by 3-5 years in males. With respect to endometrial carcinoma, female MSH6 mutation carriers had the highest risk at age 70 years (61%) compared to MLH1 (25%) and MSH2 (49%). Also, the age of EC onset was delayed by 5-10 years in comparison with MLH1 and MSH2. CONCLUSIONS: Although the cumulative lifetime risk of LS related cancer is similar, MLH1, MSH2 and MSH6 mutations seem to cause distinguishable cancer risk profiles. Female MSH6 mutation carriers have a lower CRC risk and a higher risk for developing endometrial carcinoma. As a consequence, surveillance colonoscopy starting at age 30 years instead of 20-25 years is more suitable. Also, prophylactic hysterectomy may be more indicated in female MSH6 mutation carriers compared to MLH1 and MSH2 mutation carriers.